Strategis Manajemen Kepemimpinan Kepala Sekolah dalam Implementasi Kurikulum Merdeka di Sekolah Penggerak - Romdhoni, Muhamad Febi (Lembaga Sosial Rumah Indonesia, 2024)
Purpose – The aim of this research is to examine the leadership management of school principals in implementing the Independent Curriculum at SDN Babakanpanjang.Method – The research method used is descriptive qualitative with analysis techniques based on the Miles and Huberman model involving data reduction, data presentation, and drawing conclusions. The research subjects were selected using a purposive sampling method consisting of the principal, 2 learning committees, grade 2 teachers, and grade 5 teachers at SDN Babakanpanjang.Findings – The results of the study indicate that the principal plays an important role as a motivator in developing the Independent Curriculum. This motivation is not only in the form of moral encouragement and work enthusiasm, but also in the form of concrete support such as training, awards and professional development opportunities. The principal supports teachers to take part in training and activities related to the curriculum, as well as providing motivation and supervision in making teaching modules and teaching aids. In addition, the principal also conducts periodic evaluations to assess teacher performance and the success of curriculum implementation. Research Implications – The implication of this study is the importance of principal leadership in supporting and developing the Independent Curriculum. The principal must be able to mobilize all school resources to achieve quality education goals and create a conducive and enjoyable learning atmosphere. This study provides insight for educators and policy makers about effective strategies in implementing the Independent Curriculum and Education Management in driving schools.